PENERAPAN MODEL PEMBELAJARAN STAD DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS XII MIPA 8 SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2020/2021 - I Wayan Sucipta (Widyadari : Jurnal Pendidikan, 2021)
The purpose of this study was to determine whether there was a student response and the effect of the application of the STAD learning model in improving the physics learning achievement of students in class XII MIPA 8 SMA Negeri 7 Denpasar in the academic year 2020/2021 in the Atomic Core material. This type of research is a classroom action research (PTK). Action research was carried out by means of online virtual zoom animals. In this study, the STAD (Student Team Achievement Division) type cooperative learning model was used. The study used a qualitative descriptive design with two cycles of cooperative learning model type STAD including planning, implementing, observing / evaluating and reflecting. The subjects of this study were 36 students of class XII MIPA 8 at SMA Negeri 7 Denpasar with a total of 36 students. This research was conducted at SMA Negeri 7 Denpasar. It can be concluded as follows: (1) There is an effect of the application of the STAD learning model in improving students' physics learning achievement. (2) There is a student response to physics lessons on the application of the STAD Type Cooperative learning model in improving students' physics learning achievement is good. The increase in the average value is 13.47%. The average processing of student observations from the first cycle an average of 71.55 and the average of the second cycle increased to 81.20.